Treatment of Neck Pain With Myofascial Therapies: A Single Blind Randomized Controlled Trial - Rodríguez-Huguet, Manuel; Rodríguez-Almagro, Daniel; Rodríguez-Huguet, Pablo; Martín-Valero, Rocío; Lomas-Vega, Rafael (Elsevier, 2020)
Objective This study aimed to investigate the effects of myofascial release therapy vs a standard physical therapy program in patients with neck pain (NP). Methods This was a randomized controlled trial in which 54 participants with mechanical NP were randomly assigned into an experimental group (EG) or a comparison group (CG). The EG group (n = 27) received 5 therapy sessions of myofascial release therapy while the CG group (n = 27) received 10 sessions of massage, ultrasound therapy, and transcutaneous electric nerve stimulation over a 2-week period. Outcome measures were the numerical pain rating scale (NPRS), pressure pain thresholds (PPTs) and range of motion at the end of treatment and at 1-month follow-up. Results At 1-month follow-up, between-group differences in change scores were found in the NPRS (mean = –1.56, 95% confidence interval [CI] [–2.30 to –0.81]; P < .001), in the right thoracic PPT (mean = 0.35, 95% CI [0.03-0.66]; P = .031), and in both left (mean = 0.34, 95% CI [0.08-0.61]; P = .012) and right (mean = 0.29, 95% CI [0.04-0.54]; P = .026) suboccipital PPTs. The success rate was 63.0% in the CG and 92.6% in the EG. The number needed to treat was 3.38 (95% CI = 1.99-11.23). Conclusions Myofascial release therapy could be better than a standard physical therapy program for improving pain and suboccipital PPTs in patients with NP. However, the difference between both treatments is less than the minimum detectable change of the NPRS.
Keywords: Fascia; Fisioterapia; Physical therapy modalities; Range of motion